2007
DOI: 10.1097/01.prs.0000270315.53241.10
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Digital Photography System with Computerized Eyelid Measurement Analysis

Abstract: These results suggest that a digital photography system with computer analysis is comparable to, and offers advantages over, traditional methods of measurement. This system offers a simple, standardized, and rapid method of patient assessment with important applications in electronic patient records, audit, and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 6 publications
0
26
0
3
Order By: Relevance
“…Coombes et al 27 suggested that digital photography combined with computer analysis offers an advantage over direct anthropometry; the method is simple, standardized, and documentable, and it can be applied in the research. Price et al 2 used indirect photogrammetry for measurement of eyebrows and eyelids, as we did.…”
mentioning
confidence: 99%
“…Coombes et al 27 suggested that digital photography combined with computer analysis offers an advantage over direct anthropometry; the method is simple, standardized, and documentable, and it can be applied in the research. Price et al 2 used indirect photogrammetry for measurement of eyebrows and eyelids, as we did.…”
mentioning
confidence: 99%
“…Despite the 2-dimensional nature of the measurements (a limitation that is now being overcome through the use of 3-dimensional imaging devices), digital image analysis has multiple advantages over direct measuring methods. 7,8 Although several software programs have been developed specifically to obtain anthropometric measurements, most are expensive and complex, limiting their use to particular research projects. 9 In this study, we employed an easy-to-use, inexpensive, and readily available digital imaging software, Photoshop CS3 Extended, to develop a reproducible diagram that facilitates the objective documentation and analysis of lower lid asymmetries that might need correction during a lower blepharoplasty or lateral canthopexy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Embora vários autores defendam as medidas computadorizadas (16)(17)(18) , outros (19) descreveram boa reprodutibilidade intra e inter-observador, utilizando os métodos manuais.…”
Section: Discussionunclassified
“…Há, no entanto, relato de discordância clínica entre os métodos manuais e digitais, com o último tendendo a hipoestimar a medida de FMLPS, quando comparado ao método manual (17) . No presente estudo, todas as medidas foram efetuadas por um mesmo observador experiente, em todos os intervalos de tempo.…”
Section: Discussionunclassified